Surgical Audit of Orthopaedics patients operated in covid-19 pandemic. Do patients have an increased complication rate? (Journal of Pakistan Orthopaedic Association, 2021)
Abstract:Introduction:CoVID-19 (Coronavirus disease) pandemic has involved the whole globe and exposed the limitation of health care system of different countries. Although , different countries have introduced various modalities  to protect both  general population and  health care provider to counter this world health crises but still lacked immensely leading to higher probability of contracting disease .We followed standard protocols and sharing our experience of 2688 cases. Physiological stress  compromise immunity of patient result in  increasing complications .We also determined rate of  mortality  and  infection in covid and non- covid patients.Methods: Clinical data of 2688 patients  was assessed retrospectively  who underwent orthopaedics  surgeries during the  period of COVID-19  wave in Pakistan at Ghurki Trust Teaching  Hospital in Lahore, between march 19 to June 30, 2020.Hospital protocol for Covid screening was followed including questionnaire soughting respiratory symtoms,travel history, contact history and investigations like CBC, CRP and  chest radiography. HRCT and  nasopharyngeal PCR swabs are only performed in highly suspicious patients.Results:Out of 92 highly suspicious patients ,71 came out to Covid-19 positive. Group A patients were significantly younger compared to group B (32.1±18.9 vs. 40.6±26.9, p value 0.008). There was male preponderance in both groups. Lower limb trauma constituted more than half of workload. Majority of patients were given spinal anaesthesia. Operative time was significantly higher in group B (p value